Relationship of Social Media Use (Tik-Tok) With Characters in Junior High School Grade VII in MTsN 2 Bulukumba - Sri Nurul Kurniati; Fitriani; Haerati (Comprehensive Health Care, 2021)
The current phenomenon shows how social media presents a variety of interesting applications that focus on the existence of its users from various kalanagn. Currently, social media is the most popular of various calendars, especially children, namely Tik-Tok with download data of 63.3 million users, where humans are supported by their character, making individuals have to establish social relationships with the community and social environment. Individual character is defined as behavior that is done consciously so as to form a pattern of habits.. The purpose of this study was to find out the relationshipof Tik-Tok social media use with Character in grade VII junior high school children in MTsN 2 Bulukumba.. In accordance with the problem of descriptive research correlation research methods used in this study are quantative research methods with retrospective cohort research design types that are modifications of cohort design. This design is used to determine the relationship between independent variables (risk factors) and dependent variables (outcomes) based on time travel across from the identification of risk factors to the occurrence of outcomes, but all events occurred in the past (retrospective). The study sampled 48 respondents. The data analysis in this study used the Chi-Square test. . With the statistical test used chi-square test obtained a value p : 0.449 which means there is no correlation or relationship of social media use Tik-Tok with character in children of middle age.. The conclusion of this study is the influence of tik-tok social media use on the character of junior high school age children in grade VII in MTsN 2 Bulukumba Bulukumbat district in 2021. Researchers suggest that the results of this study can be used as a reference to apply in the scope of nursing, especially for the character of children.